2013
DOI: 10.1039/c3cp51737c
|View full text |Cite
|
Sign up to set email alerts
|

A quantum chemical model for assessment of the temperature dependence in monolayer formation of amphiphiles at the air/water interface

Abstract: In the present study it is shown that parameters used in the framework of the model for the assessment of the threshold temperature of spontaneous clusterization of nonionic amphiphiles at the air/water interface (T(Cl)) are independent of the amphiphile type used in the developed schemes. The temperature dependence of the clusterization Gibbs' energies of alkyl amides, α-amino acids and 2-hydroxycarboxylic acids obtained in the framework of several schemes is listed. The exploited schemes differ from each oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…Vysotsky et al observed in their series of papers the spontaneous clustering of aliphatic amides for alkyl chain length higher than a threshold value, forming dimers and tetramers [35][36][37], Goto et al showed that during compression the hydrophilic groups are protruded in a new geometric configuration to form trilayer (or multilayer) structures [38]. Our results for the longer-chain acids are consistent with their studies.…”
Section: A Surface Pressuresupporting
confidence: 95%
“…Vysotsky et al observed in their series of papers the spontaneous clustering of aliphatic amides for alkyl chain length higher than a threshold value, forming dimers and tetramers [35][36][37], Goto et al showed that during compression the hydrophilic groups are protruded in a new geometric configuration to form trilayer (or multilayer) structures [38]. Our results for the longer-chain acids are consistent with their studies.…”
Section: A Surface Pressuresupporting
confidence: 95%
“…of this model more than ten classes of nonionic surfactants were considered, for which the threshold chain lengths were determined, which allow the formation of condensed monolayers, the "temperature effect" of clusterization, the geometric parameters of the unit cells of monolayers, the peculiarities of the dendritic film formation, the effect of the clusterization process on the pK a value. [7][8][9][10] The calculated values of the thermodynamic parameters of clusterization based on the quantum chemical approach are in qualitative agreement with the results of a thermodynamic theory, based on the use of the Volmer-type equation for the phase transition gaseous monolayer -liquid-expanded monolayer. 5 Taking into account the nonideality of the mixing entropy for monomers and clusters in the fluid-condensed transition region makes it possible to describe this region of the π-A isotherm.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptsupporting
confidence: 75%
“…The values of the free term and the slope in the eqn (17) virtually coincide within the error and for the mentioned classes of amphiphilic compounds are (10.1 AE 1.3) K and (À1.3 AE 0.2) K per CHÁ Á ÁHC interaction. 70 This reveals the same reason for the existence of the error and allows one to use the values found for the regression coefficients in the case of other surfactant classes. Corrected values of the temperature are listed in Table 4 in separate columns.…”
Section: Temperature Dependence Of Monoethoxylated Alcohol Monolayer ...mentioning
confidence: 61%